The Role of Village Funds in Improving the Quality of Public Services in Surabaya City - Nisfatul Laily Nurazizah; Diana Hertati (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study aims to analyze the strategic role of Sub-district Funds (Dana Kelurahan) in improving the quality of public services in Surabaya City through the perspectives of good governance and stewardship theory. Sub-district Funds serve as a crucial fiscal instrument for equitable infrastructure development and community empowerment at the local level. This study employs a qualitative method with a descriptive approach. Data collection was conducted through documentation studies and observations of budget realization and performance achievements across 154 sub-districts in Surabaya. The results indicate that the management of Sub-district Funds in Surabaya has been highly effective, with an average budget absorption realization reaching 94.24% in 2023. This high absorption positively correlates with improved physical environmental infrastructure and the success of economic empowerment programs, evidenced by a decrease in poverty and unemployment rates, as well as a Community Satisfaction Index (IKM) score of 95.82. In terms of governance, administrative accountability principles have been well met, although digital-based transparency still requires optimization to expand public participation access. This study concludes that Sub-district Funds function not only as financial support but also as a catalyst for community independence and increased public trust in the local government.